Edge-sharing BO4 tetrahedra and penta-coordinated silicon in the high-pressure modification of NaBSi3O8. Issue 8 (7th March 2022) - Gorelova, Liudmila; Pakhomova, Anna; Aprilis, Georgios; Yin, Yuqing; Laniel, Dominique; Winkler, Bjoern; Krivovichev, Sergey; Pekov, Igor; Dubrovinskaia, Natalia; Dubrovinsky, Leonid
Abstract : High-pressure modification of NaBSi3 O8 results in the first example of a borosilicate compound containing edge-sharing BO4 tetrahedra and SiO5 polyhedra. Abstract : The high-pressure behavior of the borosilicate reedmergnerite NaBSi3 O8 has been studied using in situ single-crystal X-ray diffraction and Raman spectroscopy up to 35 GPa. The crystal structure of NaBSi3 O8 contracts homogeneously upon compression up to 12 GPa, while at higher pressures it undergoes two phase transitions. Above 16 GPa the unit-cell volume is doubled, whereas the coordination numbers of all cations and the structural topology are preserved. Above 25 GPa the crystal structure of NaBSi3 O8 contains extremely rare dimers of edge-sharing BO4 tetrahedra and earlier unknown Si2 O5 groups consisting of edge-sharing SiO5 square pyramids. The structural model was corroborated by DFT calculations. This HP modification results in the first example of a borosilicate compound with edge-sharing BO4 tetrahedra.